KUALITAS PELAYANAN TRANSPORTASI BUS DI TERMINAL BULUPITU PURWOKERTO JAWA TENGAH - Muhammad Mughni Labib Frenanda; Sartono Sartono Sartono; Oti Kusumaningsih Kusumaningsih (Fakultas Ilmu Sosial Dan Politik, Universitas Wijayakusuma Purwokerto, 2023)
This research aims to analyze and describe the quality of bus transportation services at the Bulupitu Purwokerto terminal. The research method used is purposive qualitative research by determining the informants and purposive sampling technique. The selected informants consisted of office administration coordinators, public service sections, and community users of the Bulupitu Purwokerto terminal services. Data collection techniques use observation, interviews and documentation. Data analysis using the Interactive Analysis Model. The findings of this paper are that the quality of bus transportation services at the Bulupitu Purwokerto terminal can be assessed from several dimensions including tangibles, reliability, responsiveness, assurance and empathy. Tangibles, the availability of facilities and infrastructure such as service post rooms, counters, passenger waiting rooms, etc. and supporting facilities for the disabled are sufficient so that people who use terminal services are considered to feel that their needs are met when using services at the Bulupitu Purwokerto terminal. The reliability and punctuality of public officials when carrying out their duties according to their field is good so that the service runs optimally. Responsiveness, officers at the terminal have carried out their duties quickly and responsively according to the needs and complaints of each terminal service user. Assurance, not many people who use terminal services know that the Bulupitu Purwokerto terminal has a security services division. Empathy, the attitude of the officers at the terminal is not completely friendly, there are still some officers who seem indifferent and don't care about passengers.